RhoGTPases and inflammasomes: Guardians of effector-triggered immunity - Dufies, Océane (PLoS Pathog, 2021)
Pathogens have evolved smart strategies to invade hosts and hijack their immune responses. One such strategy is the targeting of the host RhoGTPases by toxins or virulence factors to hijack the cytoskeleton dynamic and immune processes. In response to this microbial attack, the host has evolved an elegant strategy to monitor the function of virulence factors and toxins by sensing the abnormal activity of RhoGTPases. This innate immune strategy of sensing bacterial effector targeting RhoGTPase appears to be a bona fide example of effector-triggered immunity (ETI). Here, we review recently discovered mechanisms by which the host can sense the activity of these toxins through NOD and NOD-like receptors (NLRs).